EFFECTS OF INQUIRY LEARNING MODEL ON STUDENTS' CRITICAL THINKING AND SCIENCE ACHIEVEMENT - Yani Novita Sari; Hendrizal Hendrizal; Siti Aisyah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
The purpose of this study was to analyze the effect of the inquiry learning model on critical thinking skills and learning outcomes of fourth-grade elementary school students. The research employed a quantitative approach with a quasi-experimental method using a nonequivalent control group pretest–posttest design. The population consisted of all fourth-grade students of SDIT Adzkia 1 and SDIT Adzkia 2 Padang, with a sample of 51 students selected through simple random sampling, comprising 24 students in the experimental class and 27 students in the control class. The research instrument was an essay test that had been validated in terms of validity, reliability, discrimination index, and difficulty level. Data analysis was conducted using descriptive and inferential statistics, including prerequisite tests of normality (Shapiro–Wilk) and homogeneity (Levene), followed by hypothesis testing using MANOVA at a significance level of 0.05. The results showed that the average posttest scores of critical thinking skills and learning outcomes in the experimental class (83) were higher than those of the control class (73). The MANOVA test yielded a significance value of 0.000 < 0.05, indicating that the inquiry learning model had a significant effect on students’ critical thinking skills and learning outcomes simultaneously. These findings indicate that inquiry-based learning effectively enhances students’ active engagement, analytical ability, and conceptual understanding. Therefore, the inquiry learning model is recommended as an innovative pedagogical strategy to improve the quality of science learning while fostering higher-order thinking skills in elementary school students. ABSTRAK Penelitian ini bertujuan untuk menganalisis pengaruh model pembelajaran inkuiri terhadap kemampuan berpikir kritis dan hasil belajar siswa kelas IV sekolah dasar. Penelitian menggunakan pendekatan kuantitatif dengan metode eksperimen semu (quasi experiment) melalui desain nonequivalent control group pretest–posttest. Populasi penelitian meliputi seluruh siswa kelas IV SDIT Adzkia 1 dan SDIT Adzkia 2 Padang, dengan sampel sebanyak 51 siswa yang ditentukan menggunakan teknik simple random sampling, terdiri atas 24 siswa kelas eksperimen dan 27 siswa kelas kontrol. Instrumen penelitian berupa tes esai yang telah diuji validitas, reliabilitas, daya pembeda, dan tingkat kesukaran. Analisis data dilakukan melalui statistik deskriptif dan inferensial dengan uji prasyarat normalitas (Shapiro–Wilk) dan homogenitas (Levene), serta uji hipotesis menggunakan MANOVA pada taraf signifikansi 0,05. Hasil penelitian menunjukkan bahwa rata-rata nilai posttest kemampuan berpikir kritis dan hasil belajar kelas eksperimen (83) lebih tinggi dibandingkan kelas kontrol (73). Hasil uji MANOVA menunjukkan nilai signifikansi 0,000 < 0,05, yang berarti model pembelajaran inkuiri berpengaruh signifikan terhadap kemampuan berpikir kritis dan hasil belajar siswa secara simultan. Temuan ini menunjukkan bahwa pembelajaran berbasis inkuiri efektif meningkatkan keterlibatan aktif, kemampuan analitis, dan pemahaman konseptual siswa. Model pembelajaran inkuiri direkomendasikan sebagai strategi pedagogis inovatif untuk meningkatkan kualitas pembelajaran IPA sekaligus mengembangkan kompetensi berpikir tingkat tinggi siswa sekolah dasar.